2009
DOI: 10.1038/jcbfm.2009.19
|View full text |Cite|
|
Sign up to set email alerts
|

Heme–Hemopexin Complex Attenuates Neuronal Cell Death and Stroke Damage

Abstract: Hemoproteins undergo degradation during hypoxic/ischemic conditions, but the pro-oxidant free heme that is released cannot be recycled and must be degraded. The extracellular heme associates with its high-affinity binding protein, hemopexin (HPX). Hemopexin is shown here to be expressed by cortical neurons and it is present in mouse cerebellum, cortex, hippocampus, and striatum. Using the transient ischemia model (90-min middle cerebral artery occlusion followed by 96-h survival), we provide evidence that HPX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(101 citation statements)
references
References 41 publications
8
92
1
Order By: Relevance
“…6A) (Wagner et al, 2003). Consistent with the literature (Li et al, 2009), we observed inductions of Hpx/hemopexin (2.4 Â at 4 h, 12 Â at 24 h) and Hmox1/HO-1 (3.2 Â at 4 h, 22 Â at 24 h). The gene for heme binding protein Hbp23, also known as peroxiredoxin 1, is induced 2.6 fold at 24 h (Fig.…”
Section: 5supporting
confidence: 94%
See 1 more Smart Citation
“…6A) (Wagner et al, 2003). Consistent with the literature (Li et al, 2009), we observed inductions of Hpx/hemopexin (2.4 Â at 4 h, 12 Â at 24 h) and Hmox1/HO-1 (3.2 Â at 4 h, 22 Â at 24 h). The gene for heme binding protein Hbp23, also known as peroxiredoxin 1, is induced 2.6 fold at 24 h (Fig.…”
Section: 5supporting
confidence: 94%
“…As documented in models of stroke and SAH (Li et al, 2009;Wagner et al, 2003;Wang and Dore, 2007), we observed large increases in Hpx/hemopexin and Hmox1/heme oxygenase 1 expression. The uptake and storage of iron is also tightly controlled at the posttranscriptional level by the iron-responsive element binding protein 1 (Ireb1) and 2 (Ireb2) (Pantopoulos, 2004).…”
Section: Discussionmentioning
confidence: 55%
“…However, it is also expressed in human neurons (49) and several types of mouse brain cells (26,44,48), implying that this protein is synthesized locally in brain. Interestingly, hemopexin protects the brain of adult mice against ischemic stroke-related damage in murine models (26). In addition to hemopexin, FLVCR is also present in developing mouse neural tissues and human brain tissues and cell lines (1, 2), thus providing a mechanism to remove excess heme iron from this protected site and prevent damaging iron deposits.…”
Section: Discussionmentioning
confidence: 99%
“…This protein is free of contaminants, binds heme as characterized and quantitated following published procedures and extinction coefficients (25), and is not toxic for cells (26). (27), by preloading for 30 min at 37°C using 5 M ZnMP (Frontier Scientific, Logan, UT) dissolved in cell culture-grade Me 2 SO at a concentration of 4 mM and then diluted to 5 M in working buffer (25 mM HEPES (pH 7.4), 130 mM NaCl, 10 mM KCl, 1 mM CaCl 2 , and 1 mM MgSO 4 ) containing 2.5 M BSA (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…4 This is not toxic for cells, even at supraphysiological concentrations, when incubated with primary neurons that are very sensitive to oxidative stress. 76 Heme, but not heme-HPX, produces ROS in human and mouse primary hepatocytes 14 and can induce apoptosis in both. 14 In spite of the data for intact rats with doubly labeled heme-HPX complexes, 43,65 and publications that demonstrate that heme-HPX induces HO1, 8,[77][78][79] the heme transport function of HPX has been disputed.…”
Section: Heme Delivery By Hpx With Normal Recycling Of Intact Hpxmentioning
confidence: 99%